The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-06253-0
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model analysis and numerical simulation for codynamics of meningitis and pneumonia infection with intervention

Abstract: In this paper, we have considered a deterministic mathematical model to analyze effective interventions for meningitis and pneumonia coinfection as well as to make a rational recommendation to public healthy, policy or decision makers and programs implementers. We have introduced the epidemiology of infectious diseases, the epidemiology of meningitis, the epidemiology of pneumonia, and the epidemiology of infection of meningitis and pneumonia. The positivity and boundedness of the sated model was shown. Our mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In recent years, mathematical and statistical models of infectious diseases have provided useful insights into the dynamics and control of infectious disease transmission 17 . A mathematical model of the dynamics of disease transmission is needed to provide better insight into disease behavior, optimize the use of limited resources, and recommend infectious disease control approaches 18 . A mathematical model of the infectivity dynamics of each disease is essential to gain better insight into disease behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, mathematical and statistical models of infectious diseases have provided useful insights into the dynamics and control of infectious disease transmission 17 . A mathematical model of the dynamics of disease transmission is needed to provide better insight into disease behavior, optimize the use of limited resources, and recommend infectious disease control approaches 18 . A mathematical model of the infectivity dynamics of each disease is essential to gain better insight into disease behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It can be considered as mind infection, and its expansion and impact on individuals indicted similar to infectious diseases, like tuberculosis (TB), COVID-19, and pneumonia pathogenic agents [5]. Various social science studies related to individual behaviors such as violence, racism, social media addiction, and corruption have been carried out by many scholars throughout the world [6][7][8][9][10][11][12][13][14][15]. Violence and violation are crucially at the heart of racism, and hence, in principle, the coexistence of violence and racism on individuals in a community is assured [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling has a continuous fundamental role in understanding of the various aspects of dynamical system of real-world situations like [ 17 – 21 ]. It has been formulated and analyzed in different disciplines such as natural sciences as well as social science like [ 1 5 , 9 , 22 33 ]. Many researchers have applied infectious disease dynamics model to violence, racism, social media addition, corruption, and other social situations.…”
Section: Introductionmentioning
confidence: 99%
“…Communicable diseases are clinically evident illnesses caused by microorganisms and among them; those that most common worldwide causes of death include lower respiratory infections (such as pneumonia) and HIV [12, 16, 23]. Global Burden of Diseases (GBD), 2019 study reported that lower respiratory tract infections (LRTI) including pneumonia and bronchiolitis impacted 489 million individuals in our world [21].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is the common effective method to prevent certain bacterial and viral pneumonia in both children and adults. The two types of vaccines available against streptococcus pneumoniae are the pneumococcal polysaccharide vaccine (PPV), and pneumococcal conjugate vaccine (PCV) where PCVs have been used in children only and PPV has been used for the at-risk adults and the elderly [9, 17, 23].…”
Section: Introductionmentioning
confidence: 99%